PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN SIMULASI PHET TERHADAP PENINGKATAN KEMAMPUAN MULTIREPRESENTASI KELAS XI PADA MATERI GELOMBANG MEKANIK DI SMAN 14 PEKANBARU - Putri, Reydina Aulia; Islami, Nur; Azhar, Azhar (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This research aims to determine the differences in students' multirepresentation abilities by using guided inquiry learning models assisted by PhET simulations and to determine the effect of guided inquiry learning models assisted by PhET simulations on multirepresentation abilities on mechanical wave material at SMAN 14 Pekanbaru. The type of experimental research used in this research is nonequivalent post-test only control group design. The samples in this study were XI IPA 1 class as the experimental class and XI IPA 3 class as the control class. The data collection method is by giving a post-test using a multirepresentation ability test instrument totaling 16 multiple choice questions. The data obtained were then subjected to descriptive analysis and inferential analysis. Based on the results of data processing, the average value obtained by the control class is 57.81 and the average value of the experimental class is 76.56 so that there is a difference in the multirepresentation ability of students using guided inquiry learning model assisted by PhET simulation and the application of guided inquiry learning model assisted by PhET simulation affects the multirepresentation ability of students on mechanical wave material.